Short‐ and long‐term antidepressant effects of ketamine in a rat chronic unpredictable stress model. Issue 8 (23rd June 2017) - Jiang, Yinghong; Wang, Yiqiang; Sun, Xiaoran; Lian, Bo; Sun, Hongwei; Wang, Gang; Du, Zhongde; Li, Qi; Sun, Lin
Abstract: Objective: This research was aimed to evaluate the behaviors of short‐ or long‐term antidepressant effects of ketamine in rats exposed to chronic unpredictable stress (CUS). Background: Ketamine, a glutamate noncompetitive NMDA receptor antagonist, regulates excitatory amino acid functions, such as anxiety disorders and major depression, and plays an important role in synaptic plasticity and learning and memory. Methods: After 42 days of CUS model, male rats received either a single injection of ketamine (10 mg/kg; day 43) or 15 daily injections (days 43–75). The influence of ketamine on behavioral reactivity was assessed 24 hr (short‐term) or 7 weeks after ketamine treatment (long‐term). Behavioral tests used to assess the effects of these treatments included the sucrose preference (SP), open field (OF), elevated plus maze (EPM), forced swimming (FS), and water maze (WM) to detect anxiety‐like behavior (OF and EPM), forced swimming (FS), and water maze (WM). Results: Short‐term ketamine administration resulted in increases of body weight gain, higher sensitivity to sucrose, augmented locomotor activity in the OF, more entries into the open arms of the EPM, along increased activity in the FS test; all responses indicative of reductions in depression/despair in anxiety‐eliciting situations. No significant differences in these behaviors were obtained under conditions of long‐term ketamine administration ( p  > .05). The CUS + Ketamine group showed significantly increased activity as compared with the CUS + Vehicle group for analysis of the long‐term effects of ketamine (* p  < .05). Nor were significant differences obtained in learning and memory performance in rats receiving ketamine ( p  > .05). Conclusion: Taken together these findings demonstrate that a short‐term administration of ketamine induced rapid antidepressant‐like effects in adult male rats exposed to CUS conditions, effects that were not observed in response to the long‐term treatment regime. Abstract : Administration of ketamine induced rapid antidepressant‐like effects exposed to CUS conditions. Study established the antidepressant effectiveness of ketamine with short‐term and long‐term administration. It was not obvious to improved memory and learning during short‐ and long‐term function consequences of ketamine.